2017
DOI: 10.1016/j.colsurfb.2017.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of mucoadhesive acryloyl-quaternized PDMAEMA nanogels for ocular drug delivery

Abstract: Poly((2-dimethylamino)ethyl methacrylate) (PDMAEMA) nanogels were synthesized via surfactant-free free-radical polymerization technique in aqueous conditions utilizing N,N'-methylene-bis-acrylamide (MBA) as a crosslinking agent. The PDMAEMA nanogels were subsequently quaternized with acryloyl chloride in order to yield mucoadhesive materials which incorporate two mucoadhesive concepts; electrostatic interactions and covalent bond forming acrylate groups. The native PDMAEMA nanogels were found to exhibit good m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 21 publications
2
29
0
2
Order By: Relevance
“…The intensity of these peaks decreases due to the reduction in the degree of substitution of dimethylamino groups. The appearance of a 5.98-6.44 ppm multiplet in the spectra of AEPO is generally consistent with NMR characterisation of acrylated PDMAEMA previously reported by Brannigan and Khutoryanskiy (2017), who used this method to determine the degree of acryloylation. However, unfortunately, the complex mixture of signals resulting from different repeating units of EPO leads to an overlap of many peaks; this made impossible to use 1 H-NMR spectroscopy for quantitative determination of the degrees of acryloylation.…”
Section: Characterisation Of Polymers Using Spectroscopic and Thermalsupporting
confidence: 89%
See 3 more Smart Citations
“…The intensity of these peaks decreases due to the reduction in the degree of substitution of dimethylamino groups. The appearance of a 5.98-6.44 ppm multiplet in the spectra of AEPO is generally consistent with NMR characterisation of acrylated PDMAEMA previously reported by Brannigan and Khutoryanskiy (2017), who used this method to determine the degree of acryloylation. However, unfortunately, the complex mixture of signals resulting from different repeating units of EPO leads to an overlap of many peaks; this made impossible to use 1 H-NMR spectroscopy for quantitative determination of the degrees of acryloylation.…”
Section: Characterisation Of Polymers Using Spectroscopic and Thermalsupporting
confidence: 89%
“…Previously, Brannigan and Khutoryanskiy (2017) have demonstrated that poly((2dimethylamino)ethyl methacrylate nanogels modified by reaction with acryloyl chloride exhibited greater retention on ocular mucosa compared to unmodified polymers. Similar modification is also possible for Eudragit ® EPO, Eudragit ® RL and Eudragit ® S100 copolymers containing 25 %, 10 % and 5 % of dimethylamino-groups, respectively (Mustafin, 2011;Moustafine et al, 2011;Moustafine et al, 2013).…”
Section: Synthesis Of Acrylated Epomentioning
confidence: 99%
See 2 more Smart Citations
“…These materials attract a lot of interest not only due to their mucoadhesive properties, but also because they are able to form hydrogels. Here, we will only highlight a few very recent examples in the context of adhesion to intestinal mucosa, although many interesting reports are focusing on applications such as wound dressing,43 ocular drug delivery,44 cargo delivery to different types of cancer,45 or adhesion to the tongue,46 the bladder mucosa,47 the nasal mucosa,48 or the buccal mucosa 49. For instance, the encapsulation of probiotic Lactobacillus acidophilus into alginate and chitosan‐alginate microspheres resulted in not only a slightly better mucoadhesion rate, but also in a 1.7× improved survival rate of the encapsulated probiotic compared to the free Lactobacillus acidophilus after 2 h exposure to simulated gastric fluid 50.…”
Section: Mucoadhesionmentioning
confidence: 99%